Longitudinal changes in respiratory and upper limb function in a pediatric type III spinal muscular atrophy cohort after loss of ambulation. Issue 5 (4th September 2021) - Wolfe, Amy; Scoto, Mariacristina; Milev, Evelin; Muni Lofra, Robert; Abbott, Lianne; Wake, Ruth; Rohwer, Annemarie; Main, Marion; Baranello, Giovanni; Mayhew, Anna; Marini‐Bettolo, Chiara; Muntoni, Francesco
Abstract: Introduction/Aims: Spinal muscular atrophy (SMA) type III is a relatively mild form of SMA. Few studies have investigated the changes in both respiratory and upper limb function within this population after loss of ambulation. The aim of this study was to assess change in percentage of predicted forced vital capacity (FVC% predicted) and change in the Revised Upper Limb Module (RULM) score in these patients throughout a 24‐month period after loss of ambulation. Effect of scoliosis and its surgical correction, disease duration since loss of ambulation, weight, and height were also investigated. Methods: Retrospective analyses were performed on 24 nonambulant SMA III patients from data collected at two centers in the United Kingdom. Results: The FVC% predicted score showed a significant progressive deterioration of 17% over the 24‐month period. Respiratory deterioration correlated significantly with age, weight, disease duration since loss of ambulation, and spinal correctional surgery. Longitudinal RULM data were available for 16 patients; a significant deterioration was observed with a mean decrease in score of 3 over 24 months. Age correlated negatively with RULM score, as did height and time since loss of ambulation. A significant positive correlation between FVC% predicted and RULM was demonstrated. Discussion: This study highlights how SMA type III patients have progressive deterioration of respiratory and upper limb function after loss of ambulation. Combining data from these assessments could provide insight into clinical progression, inform clinical trials, and provide assistance in managing disease progression expectations for patients.